Fixing the Problem With Empathy: Development and Validation of the Affective and Cognitive Measure of Empathy. (April 2016) - Vachon, David D.; Lynam, Donald R.
Low empathy is a criterion for most externalizing disorders, and empathy training is a regular component of treatment for aggressive people, from school bullies to sex offenders. However, recent meta-analytic evidence suggests that current measures of empathy explain only 1% of the variance in aggressive behavior. A new assessment of empathy was developed to more fully represent the empathy construct and better predict important outcomes—particularly aggressive behavior and externalizing psychopathology. Across three independent samples ( N = 210-708), the 36-item Affective and Cognitive measure of Empathy (ACME) was internally consistent, structurally reliable, and invariant across sex. The ACME bore significant associations to important outcomes, which were incremental relative to other measures of empathy and generalizable across sex. Importantly, the affective scales of the ACME—particularly a new "Affective Dissonance" scale—yielded moderate to strong associations with aggressive behavior and externalizing disorders. The ACME is a short, reliable, and useful measure of empathy.